IMPLEMENTASI PRINSIP ETIKA BISNIS ISLAM DALAM AKTIVITAS USAHA UMKM TERHADAP PELAKU USAHA KULINER HALAL - Lola Fadilah; Anggie Pratiwi; Ummy Gusti Salamah; Andry Meylani; Iga Apria (Yayasan Nusantara Hasana Berdikari, 2026)
This study aims to analyze the application of Islamic business ethics in micro, small, and medium enterprises (MSMEs) in the halal culinary sector in Indonesia. Increasing public awareness of halal products encourages business actors to not only pursue profits but also apply sharia principles in business activities. The method used is a literature study by reviewing journals, books, and scientific articles. The results of the study indicate that Islamic ethical values, such as honesty, fairness, trustworthiness, and responsibility, play a vital role in maintaining business sustainability and increasing consumer trust and loyalty. Although still facing obstacles such as limited understanding among MSMEs and regulatory support, opportunities such as halal certification, technological developments, and increasing demand for ethical products open up space for MSMEs to develop sustainably through synergy between business actors, the government, and financial institutions.